Two N-glycosylation Sites in the GluN1 Subunit Are Essential for Releasing N-methyl-d-aspartate (NMDA) Receptors from the Endoplasmic Reticulum - Lichnerova, Katarina; Kaniakova, Martina; Park, Seung Pyo; Skrenkova, Kristyna; Wang, Ya-Xian; Petralia, Ronald S; Suh, Young Ho; Horak, Martin (The Journal of biological chemistry, 2015)
NMDA receptors (NMDARs) comprise a subclass of neurotransmitter receptors whose surface expression is regulated at multiple levels, including processing in the endoplasmic reticulum (ER), intracellular trafficking via the Golgi apparatus, internalization, recycling, and degradation. With respect to early processing, NMDARs are regulated by the availability of GluN subunits within the ER, the presence of ER retention and export signals, and posttranslational modifications, including phosphorylation and palmitoylation. However, the role of N-glycosylation, one of the most common posttranslational modifications, in regulating NMDAR processing has not been studied in detail. Using biochemistry, confocal and electron microscopy, and electrophysiology in conjunction with a lentivirus-based molecular replacement strategy, we found that NMDARs are released from the ER only when two asparagine residues in the GluN1 subunit (Asn-203 and Asn-368) are N-glycosylated. Although the GluN2A and GluN2B subunits are also N-glycosylated, their N-glycosylation sites do not appear to be essential for surface delivery of NMDARs. Furthermore, we found that removing N-glycans from native NMDARs altered the receptor affinity for glutamate. Our results suggest a novel mechanism by which neurons ensure that postsynaptic membranes contain sufficient numbers of functional NMDARs.
Keywords: Animals; Golgiho aparát; Chlorocebus aethiops; HEK293 Cells; Glycosylation; N-Methylaspartate; polysacharidy; synapse; lidé; Endoplasmic Reticulum; COS Cells; neurony; Golgi Apparatus; COS buňky; HEK293 buňky; N-methylaspartát; Neurons; Receptors, N-Methyl-D-Aspartate; glykosylace; nervový přenos; Synaptic Transmission; krysa rodu Rattus; receptory N-methyl-D-aspartátu; Cercopithecus aethiops; zvířata; Synapses; endoplazmatické retikulum; Polysaccharides; Rats; Humans